Fracture Mapping of Both-Column Acetabular Fractures. Issue 5 (May 2022) - Yin, Yingchao; Zhang, Ruipeng; Hou, Zhiyong; Fan, Shicai; Zhuang, Yan; Yi, Chengla; Chen, Hua; Zhang, Yingze
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To characterize the location and frequency of the fracture lines and comminution zones of both-column fractures using fracture mapping. Methods: Both-column fractures were retrospectively reviewed in 4 Level 1 trauma centers. Mimics software was used to reconstruct the both-column fractures and simulate the fracture reduction. Then, the fracture lines and the intra-articular and extra-articular comminution zones were drawn on a 3-dimensional innominate bone template. The distribution of fracture lines and fracture fragments were also mapped on the two-dimensional template of the acetabulum. All the included patients were divided into low-variety group and high-variety group according to the anterior column fracture line above or below the anterior superior spine. The anatomical characteristics of the posterior wall fragment were also analyzed in these 2 groups. Results: Seventy-eight patients with both-column fracture were included. The T type or inverted Y type main fracture lines divided the innominate bone into low-variety (n = 11) and high-variety (n = 67) both-column fractures. The extra-articular comminution zones are usually distributed between the posterior iliac fragment and anterior column fragment. High-variety type both-column fractures are usually combined with high and sharp posterior wall fragments, whereas low-variety type both-column fractures are usually accompanied by low and flat posterior wall fragments. The comminution zones in the acetabulum are mostly concentrated in the anterior and inferior parts of the acetabulum. Conclusions: The innominate bone is divided into 3 major parts in the both-column fracture, and the fracture center is located at the proximal of the acetabular dome. The both-column fractures are divided into low-variety and high-variety patterns. The location of the anterior column fracture determined the characteristics of the posterior wall fragment.